2019
DOI: 10.4314/tjpr.v17i12.9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cytotoxic effects of sodium hypochlorite on human dental stem cells

Abstract: Purpose: To investigate the influence of sodium hypochlorite (NaOCl) on human dental stem cell proliferation and differentiation. Method: Dental pulp stem cells (DPSCs), periodontal ligament stem cell (PDLSCs), and gingival mesenchymal stem cells (GMSCs) were treated with NaOCl. Cell viability was evaluated with cellular counting kit-8 (CCK8), and cellular adenosine triphosphate (ATP) levels were analyzed by bromodeoxyuridine (BrdU) incorporation and subsequent flow cytometry. Quantitative polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
2
11
0
1
Order By: Relevance
“…Similarly, NaOCl with a concentration of 6% was reported to have devastating effects on MSCs, while NaOCl with a concentration of 1.5% had lesser negative effects (4). In another in vitro study, it was shown that NaOCl negatively affects viability, proliferation capacity and differentiation potential, and this effect is time and concentration dependent (20). In this study, 100‐fold dilution of 6% NaOCl did not create a significant reduction in the viability of MSCs in 10‐ and 60‐min exposures compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, NaOCl with a concentration of 6% was reported to have devastating effects on MSCs, while NaOCl with a concentration of 1.5% had lesser negative effects (4). In another in vitro study, it was shown that NaOCl negatively affects viability, proliferation capacity and differentiation potential, and this effect is time and concentration dependent (20). In this study, 100‐fold dilution of 6% NaOCl did not create a significant reduction in the viability of MSCs in 10‐ and 60‐min exposures compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies observed that DPSCs did not attach to the dentin surfaces treated by 5.25% [27,30], and 6% of NaOCl [24]. Moreover, an in vitro study demonstrated that NaOCl can deteriorate viability, proliferation and differentiation of dental-derived MSCs, such as DPSCs, PDLSCs, and GMSCs in concentration-and time-dependent manner [34].…”
Section: Sodium Hypochlorite (Naocl)mentioning
confidence: 97%
“…Sodium Hypochlorite (NaOCL) is used as main irrigant due to its antimicrobial ability and unique organic tissue dissolving action. However, it has been found that it decreases the viability of the stem cells in concentration and time dependent manner (13) . NaOCl to be effective, its application time should be about 5 minutes (4) .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that 17% EDTA can be used as disinfectant (14) . It has been found that 17% EDTA affects the physicochemical properties of dentin, like changes in chemical composition, topography and wettability which in turn affects the attachment of stem cells to dentin (13) .…”
Section: Introductionmentioning
confidence: 99%